2022
DOI: 10.4018/ijmmme.296277
|View full text |Cite
|
Sign up to set email alerts
|

Formability of Aluminum Alloys During Single Point Incremental Forming

Abstract: Single point incremental sheet metal forming has passed through a period of ample improvement with developing responsiveness from research societies and industries globally. The process has expressively spared the practice of using costly dies, which makes it an appropriate process for manufacturing prototypes and small batch production. It also discovers easiness in fabricating components of timeworn equipment. Additionally, in recent years, aluminum alloys become the most commonly used materials in the autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Dabwan et al (2020) also said smaller step size (SS) was favorable for higher accuracy. Bishnoi and Chandna (2022a) concluded that smaller vertical SS and higher tool rotation speeds (TRSs) are favorable conditions for forming superalloy 625 components with higher geometric accuracy. Radu and Cristea (2013) demonstrated that during SPIF of products, a greater feed rate reduces part accuracy and higher tool rpm stimulates part accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabwan et al (2020) also said smaller step size (SS) was favorable for higher accuracy. Bishnoi and Chandna (2022a) concluded that smaller vertical SS and higher tool rotation speeds (TRSs) are favorable conditions for forming superalloy 625 components with higher geometric accuracy. Radu and Cristea (2013) demonstrated that during SPIF of products, a greater feed rate reduces part accuracy and higher tool rpm stimulates part accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…To form the product, the sheet blank is fixed at an exact height in a specially designed fixture, and the CNC tool is moved in a predefined toolpath. The SPIF technique was first used to create metallic components (Pandivelan and Jeevanantham, 2015; Bishnoi and Chandna, 2022b), but researchers later used it to create shape-memory materials, sandwich and laminated sheets, composites, polymers and superalloys parts (Jackson, Allwood and Landert, 2008; Mohammadi et al , 2015; Centeno et al , 2017; Liu and Li, 2019; Wu et al , 2019; Bishnoi and Chandna, 2022a). Because the SPIF method is not affected by the work material’s chemical, electrical or thermal properties, it may be used in the transportation, solar, aerospace, medical, automotive and architectural sectors (Duflou et al , 2008; Trzepieciński et al , 2018; Bishnoi and Chandna, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging forming method known as the single-point incremental forming (SPIF) process has several advantages over classic sheet metal forming practices that can be implemented to address these issues. SPIF is especially beneficial in rapidly prototyping and manufacturing custom-made products for the aerospace, automotive, architectural and biomedical sectors (Trzepieciński et al , 2018; Bishnoi and Chandna, 2022). In the SPIF process, the smaller region of the workpiece is uninterruptedly deformed by the tool in a three-axis computer numerical controlled (CNC) machine till it procures the final shape according to the preset toolpath.…”
Section: Introductionmentioning
confidence: 99%